Reversible median nerve neuropathy and local muscle irritation resulting from blind removal attempts of etonogestrel contraceptive implant: a case report - Siraphat Fungtammasan; Natchanika Sinthuchai; Kawee Pataradool; Unnop Jaisamrarn; Somsook Santibenchakul (BMC, 2023)
Abstract Nexplanon is an etonogestrel contraceptive implant that comes with an applicator, making it easier to insert and remove. Complications related to insertion and removal procedures, such as neural-vascular injuries, are rare. We describe a case of reversible median nerve neuropathy and local muscle irritation resulting from blind removal attempts of an iatrogenically migrated implant. The patient presented with an unusual pain at the surgical site along with abnormal sensations and numbness in her left hand that worsened after blind attempts to remove the implant. Radiographs revealed that the rod was 3 cm from her insertion scar and deeply embedded in her left arm. The patient then underwent left arm exploration and implant removal under fluoroscopic guidance by an orthopedic surgeon. The rod was placed intramuscularly, adjacent to the median nerve under the basilic vein. The abnormal sensations and numbness in her left hand could be attributed to median nerve involvement, while the atypical pain at the surgical site could be a result of local irritation from the intramuscularly migrated implant from attempts at removal. The symptoms gradually resolved after surgery. This indicates that patients with impalpable contraceptive implants should be referred for implant removal by specialists familiar with the procedure to prevent further deterioration of adjacent structures from iatrogenic implant migration.